The effects of the training in the preparation period on the coordination transformation with football players U16 - Gardasevic, J.; Vasiljevic, I. (Kinesiologia Slovenica, 2017)
The main aim of the research was to identify a level of quantitative changes of the coordination with fifteen years old football players under the influence of the programmed football training of a six weeks preparation period. The training programme covered forty-four training units. The research was made on a sample of 120 cadet level football players. To estimate the coordination three tests have been used: Eight with bending, Steps aside and Legs slalom off with two balls. In the area of comparative statistics, we used discriminant parametric procedure t-test for big paired samples. It can be concluded that there are statistically significant differences in all three variables to estimate the coordination. This confirmed the hypothesis that the expected significant positive quantitative changes of coordination influenced by the proposed model of training in preparation period with fifteen years old football players. The authors were guided by the fact that this kind of training program in preparation period is very effective in terms of raising the coordination level with fifteen years old. The obtained results can be directed towards innovation plans and programs in the preparation period, and the adaptation of the same needs of the respective population.